The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1016/s0012-1606(03)00355-5
|View full text |Cite
|
Sign up to set email alerts
|

Progression of calvarial bone development requires Foxc1 regulation of Msx2 and Alx4

Abstract: Calvarial bones form by direct ossification of mesenchyme. This requires condensation of mesenchymal cells which then proliferate and differentiate into osteoblasts. Congenital hydrocephalus (ch) mutant mice lack the forkhead/winged helix transcription factor Foxc1. In ch mutant mice, calvarial bones remain rudimentary at the sites of initial osteogenic condensations. In this study, we have localized the ossification defect in ch mutants to the calvarial mesenchyme, which lacks the expression of transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
151
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(164 citation statements)
references
References 42 publications
10
151
2
Order By: Relevance
“…The mechanism by which Foxc1 regulates skeletal development has previously been investigated from the viewpoint of intramembranous bone formation with particular focus on osteoblasts, not endochondral ossification. Thus, several groups have reported the importance of bone morphogenetic protein signalling and Msx2 in Foxc1-dependent calvarial bone development [46][47][48] . Although Alcian blue-positive nodule formation of mesenchymal cells isolated from Foxc1 lacZ embryos has been studied 45 , the molecular mechanisms by which Foxc1 controls endochondral formation are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which Foxc1 regulates skeletal development has previously been investigated from the viewpoint of intramembranous bone formation with particular focus on osteoblasts, not endochondral ossification. Thus, several groups have reported the importance of bone morphogenetic protein signalling and Msx2 in Foxc1-dependent calvarial bone development [46][47][48] . Although Alcian blue-positive nodule formation of mesenchymal cells isolated from Foxc1 lacZ embryos has been studied 45 , the molecular mechanisms by which Foxc1 controls endochondral formation are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have indicated that Msx2 plays a critical role in the proliferation of osteoprogenitor cells in the osteogenic fronts of the suture area (22,33). The cranial suture is a mass of soft tissue between two calvarial bones and is the growing front of the calvarial flat bones.…”
Section: Discussionmentioning
confidence: 99%
“…BMP2 and BMP4 stimulate cranial suture closure by activating their downstream targets Dlx5 (Holleville et al, 2003) and Msx2 (Rice et al, 2003). Our recent report indicates that the expression of the osteogenic master transcription factor, Runx2, is stimulated by BMP signaling and that Dlx5 mediates this signaling process (Lee et al, 2003a).…”
Section: Introductionmentioning
confidence: 98%